(untitled) (Research, Society and Development, 2025)
For a long time, non-communicable chronic diseases suffered from a scarcity of therapies that could provide patients with a significant improvement in quality and life expectancy, as well as reduce the direct and indirect complications of their underlying clinical conditions. With the advent of SGLT2 inhibitors (sodium-glucose co-transporter 2 inhibitors), promising results have been found based on these objectives, including a paradigm shift in the natural course of chronic kidney disease and in the field of nephrology as a specialty. The aim of this study is to contribute as a tool for knowledge building on the topic, to describe some of its applications in medical practice, and additionally, to create space for filling gaps that have yet to be explored. For this purpose, a narrative literature review was conducted, containing articles and guidelines published and available in electronic databases over the last 10 years. After the selection of texts, it was possible to perceive the variety of applications and the current impact this class of medications has brought to clinical practice. Furthermore, after the production of the text, it is evident that many gaps still exist that can be filled and explored on the subject.